DAMPAK PERKEMBANGAN BUDAYA MODERN TERHADAP EKSISTENSI BUDAYA LOKAL DI ACEH (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2020)
The development of culture are a thing is not possible to evade, with of development of information technologies the development of culture has expanded until everywhere, even can change purity local culture where new culture came including also in culture local Aceh though .This discussion aims to look at about the influence of modern culture to existence local culture aceh that flourish with of development of information technologies .Discussion this was done in review texts and the results of research having relevance for the purpose subjects, writer take some forms of the development of culture and an effect on cultural took. Discussion results found that cultures aceh by deliberately is shifting and the community aceh by receptive the new culture , are evident in the form of intercommunication youth, degradation moral, divorce rates and affair, style intercommunication and social interaction s broader. Change and development of this culture has to be early protection for all stakeholders in Aceh to bore filterisasi culture to local culture Aceh in which to come.